PRETREATMENT OF LIGNOCELLULOSIC BIOMASS WITH AUTOCHTHONOUS SFUNGI FROM SERBIA - Jović, Jelena; Kocić-Tanackov, Sunčica; Mojović, Ljiljana (Journal on Processing and Energy in Agriculture, 2021)
This research examined the potential use of isolated Serbian autochthonous fungi in lignocellulosic biomass pretreatment. Among 12 isolated fungi, the isolates identified as Trametes hirsuta F13 and Stereum gausapatum F28 stood out as ligninolytic enzyme producers and were selected for potential use in the pretreatment of a waste lignocellulosic biomass. An isolate identified as Myrmaecium fulvopruinatum F14 showed high hydrolytic activity, but negligible ligninolytic activity, and it was selected as a potential producer of important industrial hydrolytic enzymes.Further, the breakdown of lignocellulosic waste, beechwood sawdust, by T. hirsuta F13 and S. gausapatum F28 was examined. Both isolates efficiently degraded biomass, but T. hirsuta F13 exhibited greater selectivity (selectivity coefficient of 1.7) than S. gausapatum F28 (1.1). The isolate F13 was considered a better candidate for the pretreatment, and it was selected for further analysis which involved the use of molasses stillage as a supplement to improve the pretreatment.
Keywords: autochthonous fungi, lignocellulose, laccase, manganese peroxidase, cellulase, xylanase